2003
DOI: 10.1053/jlts.2003.50199
|View full text |Cite
|
Sign up to set email alerts
|

Preoperative liver donor evaluation: Imaging and pitfalls

Abstract: This article discusses the rationale behind living (related) donor liver transplantation, the role of imaging in the preoperative evaluation of the potential donor, and the currently available imaging modalities for fulfilling this task. Furthermore, the normal hepatic vascular and biliary anatomy, as seen on imaging, is reviewed and the most common anomalies are highlighted. Finally, critical concepts in the diagnostic evaluation of a donor are discussed with special emphasis on how to accurately measure live… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
34
0
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 49 publications
(36 citation statements)
references
References 39 publications
1
34
0
1
Order By: Relevance
“…However, Schroeder et al [4] found CT to be more accurate in detecting variations in vascular anatomy. This is probably related to the inherently superior spatial resolution of CT compared to MR. Hepatic artery thrombosis (HAT) is one of the most dreaded complications of LT and can be drastically decreased by excluding grafts with unfavorable anatomy [27] . In the past, a potential graft with a narrow hepatic artery of less than 2 mm in diameter was regarded as a contraindication for LDLT due to the high risk of HAT.…”
Section: Hepatic Arterial Systemmentioning
confidence: 99%
See 3 more Smart Citations
“…However, Schroeder et al [4] found CT to be more accurate in detecting variations in vascular anatomy. This is probably related to the inherently superior spatial resolution of CT compared to MR. Hepatic artery thrombosis (HAT) is one of the most dreaded complications of LT and can be drastically decreased by excluding grafts with unfavorable anatomy [27] . In the past, a potential graft with a narrow hepatic artery of less than 2 mm in diameter was regarded as a contraindication for LDLT due to the high risk of HAT.…”
Section: Hepatic Arterial Systemmentioning
confidence: 99%
“…This is best evaluated on a non-contrast study as relative densities of the liver and spleen can vary on post contrast scans depending on the phase of image acquisition [27] . The attenuation value of normal liver on unenhanced CT ranges between 55 and 65 Hounsfield units (HU) and is generally at least 8 HU higher relative to the spleen; the liver is regarded as fatty when the liver attenuation is at least 10 HU less than the spleen [59] .…”
Section: Hepatic Parenchymamentioning
confidence: 99%
See 2 more Smart Citations
“…During the last few years, computer-aided surgical planning systems (CAD) have contributed significantly in diagnosing and treatment of liver diseases [3]. These cutting-edge methods portray the structure of liver and its vessels often in the form of 3D visualizations, provide insights into surgical simulations with cutting guidelines.…”
Section: Introductionmentioning
confidence: 99%